Pemberdayaan Masjid sebagai Pusat Literasi Keagamaan di Desa Sahang (Studi Kasus di Masjid Thariqotul Huda Dusun Ngrambing, Desa Sahang, Kecamatan Ngebel) - Hafidz Ihsan Maulana; Asaduddin Luqman (Social Science Academic, 2025)
Mosques are places of worship for Muslims. Besides being used as places of worship, mosques also serve as centers for religious literacy and religious-based learning within the community. The purpose of this community service is to determine how to empower mosques as centers of religious literacy in Sahang Village. The ABCD method is the method used in analyzing the research in this community service. By focusing on identifying and utilizing local assets, strengths, and potential for sustainable empowerment. The results of this community service are that empowerment activities can increase community knowledge of religion and increase community participation in the importance of congregations at the mosque. However, on the other hand, there are obstacles and challenges such as the difficulty of inviting people to go to the mosque and the cultural conditions in the area that greatly influence.